Mountaineering women : stories by early climbers - Mazel, David (Texas A & M University Press, 1994)
"Women have known the challenges and triumphs of mountaineering for nearly two centuries, and for nearly as long they have been writing about their accomplishments, creating a fascinating, often thrilling literature of adventure and daring. As with other aspects of women's history, however, the literature of mountaineering women has been scattered and largely forgotten. Sixteen of their stories - sometimes published under the name of a male relative, sometimes under anonymous bylines such as "a Lady"--Are here recovered and collected for the first time." "The women who speak to us in this book climbed on the world's highest peaks and most difficult rock faces, from the English Lake District to the Alps to the Andes and Himalaya. Some were politically motivated, like the American Annie Smith Peck, who considered her spectacular ascents a strategy for advancing the liberation of her sex. Others were staunchly conservative about all matters save their personal right to climb mountains, a right that could rarely be taken for granted and sometimes proved as difficult to win as the summit itself." "These stories are as much about people as about mountains. They tell of conflict and cooperation, of women struggling not only to reach a summit but also to negotiate their freedom in a society that preferred they simply stay at home. The editor's introduction provides an overview of the two hundred-year history of women's climbing and places it in the context of that struggle." "Mountaineering Women shows how highly skilled, courageous, and determined women have revised and transformed a traditionally masculine activity, while at the same time transforming themselves - each arriving, as Mary Crawford put it, "at last upon the summit to gaze out upon a new world. Surely not the same old earth she has seen all her life? Yes - but looked at from on top - a point of view which now makes upon her mind its indelible impression.""--Jacket